2010
DOI: 10.1177/0898264310362541
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Comparison of the Perceptions and Experiences of Dementia Care Mapping “Mappers” in the United States and the United Kingdom

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…As with a previous surveys of DCM users (21), this study found that a number of those trained do not go on to use DCM afterwards. This study showed a slightly higher percentage of respondents who had used DCM (60%) than in previous studies (50% in UK and 30% in US).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As with a previous surveys of DCM users (21), this study found that a number of those trained do not go on to use DCM afterwards. This study showed a slightly higher percentage of respondents who had used DCM (60%) than in previous studies (50% in UK and 30% in US).…”
Section: Discussionsupporting
confidence: 80%
“…Increased time and resources were identified by the vast majority of mappers as being something that would increase mapping activity in their organisation, whether or not they had previously mapped, indicating that this remains an issue even in settings where mapping does occur. A lack of time and resources is commonly cited within health and social care as a barrier to delivery of person-centred care and to the utilisation of quality monitoring and improvement tools and processes (21). This study shows that despite limited resources some organisations are able to support regular DCM activity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…() observed the importance of the commitment of team managers and Douglass et al . () identified organisational backing as a facilitator of DCM implementation. Scurfield‐Walton () argued that isolated DCM interventions will not be able to implement PCC and that DCM needs to be integrated using a precise implementation plan that considers aspects of team development.…”
Section: Discussionmentioning
confidence: 99%
“…Person‐centred care is based on the concept of personhood, “a socially created entity established through the action of others” (Douglass, Keddie, Brooker, & Surr, , p.568). Person‐centred care is the maintenance of an individual's personhood, through the context of personal and social relationships (Kitwood, ).…”
Section: Introductionmentioning
confidence: 99%